The influence of trimetazidine hydrochloride on acute ischemia-reperfusion injury of endothelial cells and oxidative stress response of rat kidney - DU Yi; QIAN Bai-yin; LI Su-xia; LI Mi (Linchuang shenzangbing zazhi)
Objective To observe the effects of trimetazidine(TMZ)preconditioning on endothelial cell injury and oxidative stress in rats with acute renal ischemia-reperfusion.Methods 90 SD rats were randomly divided into A and B groups.Group A was given TMZ at a dose of 10 mg/kg.After lavaged for 5 days,ischemia-reperfusion injury(IR1),ischemic postconditioning(IPO1),sham operated(S1)were established.In the same way,the IR2,IPO2 and S2 were established in group B after 5 days of saline enema.The levels of serum creatinine(SCr),urea nitrogen(BUN),vascular cell adhesion molecule 1(VCAM-1),malondialdehyde(MDA)superoxide dismutase(SOD)were measured at 0,6,12,24 and48 h after the last recovery of kidney blood supply in each group.Results Compared with IR1 group,the levels of VCAM-1,MDA at 6 h and BUN,SCr,VCAM-1,MDA and renal tubular injury score at 24 and 48 h in IR2 group were significantly higher than those in IR1 group,while SOD was decreased;Compared with IPO1 group,the levels of VCAM-1 and MDA at 6,12 and 24 h and BUN,SCr and renal tubular injury score at 24 h in IPO2 group were significantly increased,while SOD was decreased at 6,12 and 24 h;Compared with IPO1,apart from SCr,the levels of BUN,VCAM-1,MDA and renal tubular injury score at 24 h in IR1 group were increased and the levels of VCAM-1,renal tubular injury score at 48 h in IR1 group were significantly increased,and SOD was decreased at both time points;Compared with IR1 group,the levels of VCAM-1,MDA and renal tubular injury score at 12 and 24 h in IPO2 group were increased,while SOD were decreased and apart from MDA,the levels of BUN,SCr,VCAM-1 and renal tubular injury score at 48 h in IPO2 group were significantly increased,while SOD was decreased(P>0.05).Conclusions Compared with IPO alone,using TMZ can reduce the oxidative stress response and decrease the serum VCAM-1 level before the occurrence of IR in rats.